Posterior spinal fusion formation depending on different physical activity in animals - Radchenko, Volodymyr; Skidanov, Artem; Ashukina, Nataliya; Danishchuk, Zinayda; Levytskyi, Petr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
Structural violations in paravertebral muscles — spinal units stabilizators, are related to the risk factors for degenerative lumbar spane diseases. Experts pay attention to their condition after the surgical treatment — spinal fusion. However effect of muscle activity on the result of surgical treatment is not studied well. Subject: to evaluate results of posterior spinal fusion and lumbar transpedicular spinal fusion in rats depending on animals muscle activity. Methods: experiment is carried out in 20 laboratory rats (age 5 month, weight from 430 to 500 gr.) with were divided in to four groups, 5 animals in each, depending on the physical activity level. Animals swam before and after (I), before (II), after (III) the surgery and didn’t swim (IV). Vertebral bodies of adjacent LІV, LV bodies fixed using author’s method with transpedicular instrumentation and bone autoplasty. After 3 month postoperatively bone fusion formation analyzed using clinical, radiographic and histological data. Significance of interrelations between quality signs (physical activity pattern and surgical results) evaluated on the basis of contingency tables. Results: bone fusion formation confirmed clinicaly and radiographically after 3 month postoperatively found in 60% (II group), 40% (III), 20% (IV) and 80% (I). It is observed histological signs of significant bone formation in spinous process, spreading into inter laminar spaces that joins vertebras between. Conclusion: it is found positive effect of physical stresses (swimming) on bone fusion formation (G = 0.671642, р = 0.013097). The best results achieved in the animals group who swim with high level of physical activity (swam before and after the surgery).